Mineral phase transformation of biomass ashes – Experimental and thermochemical calculations. (December 2018) - Magdziarz, Aneta; Gajek, Marcin; Nowak-Woźny, Dorota; Wilk, Małgorzata
Abstract: The paper is focused on the thermal characterisation of biomass ashes especially of mineral phase transformation. Ash generated during combustion (with high alkali metal concentration) can deposit and consequently cause serious operating problems such as slagging, fouling and corrosion of metal surface limiting heat transfer. Four biomass ashes with different origin were investigated. The chemical composition of the mineral matter of ashes varied between the samples, but CaO, SiO2, K2 O, MgO, P2 O5 and Al2 O3 are the main compounds of the ashes. The thermal behaviour of ashes was studied using TG-DSC and Ash Fusion Temperatures (AFTs) techniques. In order to describe and understand the mineral matter transformation at high temperatures the FactSage Thermodynamics Model was used. FactSage calculations allowed to predict chemical composition in equilibrium, showed amount of liquid slag and solid phases, and gave information about slagging properties of ashes. A corrosion study of the metal surface used for heat transfer biomass ashes was undertaken. The corrosion behaviour of steel X10CrMoVNb9-1 in the present of biomass ash at 650 °C in 1000 h in furnace. The degradation of the metal surface was investigated by observation of surface morphology using the SEM method. The presence of potassium and chlorine in deposits causes the acceleration of oxidation. They break and peel off the surface easily, thus evidently accelerating corrosion. Highlights: Characterisation of biomass ashes were given. Transformation of inorganic components was determined using TGA, XRD, and SEM. The ash fusion behaviour of ashes was studied experimentally. Thermodynamic equilibrium calculation (FactSage) was used. Corrosive properties of biomass ash were investigated.